Controlling protein interactions in blood for effective liver immunosuppressive therapy by silica nanocapsules - Jiang, Shuai (2020)
Immunosuppression with glucocorticoids is a common treatment for autoimmune liver diseases and after liver transplant, which is however associated with severe side-effects. Targeted delivery of glucocorticoids to inflammatory cells, e.g. liver macrophages and Kupffer cells, is a promising approach for minimizing side effects. Herein, we prepare core–shell silica nanocapsules (SiO2 NCs) via a sol–gel process confined in nanodroplets for targeted delivery of dexamethasone (DXM) for liver immunosuppressive therapy. DXM with concentrations up to 100 mg mL−1 in olive oil are encapsulated while encapsulation efficiency remains over 95% after 15 days. Internalization of NCs by non-parenchymal murine liver cells significantly reduces the release of inflammatory cytokines, indicating an effective suppression of inflammatory response of liver macrophages. Fluorescent and magnetic labeling of the NCs allows for monitoring their intracellular trafficking and biodegradation. Controlled interaction with blood proteins and good colloidal stability in blood plasma are achieved via PEGylation of the NCs. Specific proteins responsible for stealth effect, such as apolipoprotein A-I, apolipoprotein A-IV, and clusterin, are present in large amounts on the PEGylated NCs. In vivo biodistribution investigations prove an efficient accumulation of NCs in the liver, underlining the suitability of the SiO2 NCs as a dexamethasone carrier for treating inflammatory liver diseases.